Mechanical induction in metazoan development and evolution: from earliest multi-cellular organisms to modern animal embryos - Ngoc Minh Nguyen; Emmanuel Farge (Nature Communications)
Abstract The development and origin of animal body forms have long been intensely explored, from the analysis of morphological traits during antiquity to Newtonian mechanical conceptions of morphogenesis. Advent of molecular biology then focused most interests on the biochemical patterning and genetic regulation of embryonic development. Today, a view is arising of development of multicellular living forms as a phenomenon emerging from non-hierarchical, reciprocal mechanical and mechanotransductive interactions between biochemical patterning and biomechanical morphogenesis. Here we discuss the nature of these processes and put forward findings on how early biochemical and biomechanical patterning of metazoans may have emerged from a primitive behavioural mechanotransducive feeding response to marine environment which might have initiated the development of first animal multicellular organisms.